Решение:1) (a + b)^2 - (a - c)^2 = a^2 + 2ab + b^2 - (a^2 - 2ac + c^2) = a^2 + 2ab + b^2 - a^2 + 2ac - c^2 = 2ab + b^2 + 2ac - c^2.2) (a + b)^2 - (b + c)^2 = a^2 + 2ab + b^2 - (b^2 + 2bc + c^2) = a^2 + 2ab + b^2 - b^2 - 2bc - c^2 = a^2 + 2ab - 2bc - c^2.3) (2a + b)^2 - (2b + a)^2 = 4a^2 + 4ab + b^2 - (4b^2 + 4ba + a^2) = 4a^2 + 4ab + b^2 - 4b^2 - 4ba - a^2 = 4a^2 + b^2 - 4b^2 - a^2 =3a^2 - 3b^2.4) (a - 3b)^2 - (3a + b)^2 = a^2 + 6ab + 9b^2 - (9a^2 + 6ab + b^2) = a^2 + 6ab + 9b^2 - 9a^2 - 6ab - b^2 = - 8a^2 + 8b^2.